Microstructure of additive manufactured inconel 718 using electron beam melting - Lim, Sebastian Hui Bo (Nanyang Technological University, 2020)
Electron Beam Melting is a form of additive manufacturing that uses an electron beam to produce 3D structures. Due to its capability of forming complex shapes and reducing the amount of material wastage, it appeals to industries. However, despite its advantages, electron beam melting still had issues of producing objects with homogenous microstructure throughout the build, with many research studies focusing on altering the printing parameters. As such, double melting was investigated, where two plates with similar printing parameters were printed close to one another forming a double melt region in the middle of the 2 plates. The microstructure and types of phases of 2 different sizes of double melt regions (3.5 mm and 0.7 mm) were investigated using the Electron Backscattered Diffraction, Scanning Electron Microscopy, and Optical microscope. The results showed that double melting does affect the microstructure and types of phases present in Electron Beam melted Inconel 718 depending on the size of the double melt region.